Effect of Substitution of Beef and Broiler Meat with Tuna Meat on Chemical and Sensory Quality of Meatballs - Tiven, Nafly Comilo; Simanjorang, Tienni Mariana (Food technology and biotechnology, 2024)
Research background. Tuna meat is rich in protein and polyunsaturated fatty acids (PUFA), but low in cholesterol and fat, which makes it an excellent candidate for replacing beef and broiler chicken to produce higher quality meatballs. The aim of this study is to determine how substituting beef and broiler meat with tuna meat affects the chemical and sensory characteristics of meatballs. Experimental approach. In this study, 1000 g of meatballs were prepared from 60 % of beef or broiler chicken. Each meat was replaced with tuna meat at mass fractions of 0, 20 and 40 %. The meat was finely ground and mixed with mass fractions (in %) of: tapioca flour 20, garlic 1.2, salt 2, ground pepper 0.5, egg white 0.3 and ice cubes 16. The tested variables included the chemical quality (moisture, protein, fat, ash, cholesterol and fatty acids) and sensory quality (colour, aroma, elasticity, texture and taste) of the meatballs. The data obtained were statistically analysed using a completely randomised factorial design analysis of variance. Results and conclusions. The results show that increasing the mass fraction of tuna as a substitute for beef and broiler meat significantly increased (p<0.01) the moisture, protein and PUFA mass fractions and colour, but decreased (p<0.01) the cholesterol and fat mass fraction of the meatballs. A significant interaction (p<0.01) was observed between the tuna mass fraction and the type of meat, which affected the mass fractions of moisture, protein, cholesterol and fat as well as colour of the meatballs. In particular, increasing the tuna mass fraction to 40 % significantly increased (p<0.01) the moisture mass fraction of the beef meatballs, as well as the protein mass fraction and colour of the beef and chicken meatballs. However, the moisture mass fraction of chicken meatballs and the fat and cholesterol mass fraction of beef and chicken meatballs decreased significantly (p<0.01). In conclusion, replacing 40 % of beef and chicken meatballs with tuna can improve protein content and colour, and reduce fat and cholesterol content. Novelty and scientific contribution. These results suggest that tuna can be used as a substitute for beef and chicken to produce higher quality meatballs that are rich in protein but low in cholesterol and fat. This approach can also be applied to other processed meat products such as sausages and nuggets to improve their nutritional quality.